Effect of education based on theory of planned behavior in healthy cooking - Rabea Agh Atabay; Mahnaz Shahrakipoor; Farzane Montazerifar; Iraj Zareban (Gonabad University of Medical Sciences, 2017)
Healthy eating habits can reduce the risk of several chronic diseases and decrease overall mortality in women by 11%. Regarding the crucial role of women in feeding the family, we investigated the effect of education in healthy cooking behavior of rural women by applying the Theory of Planned Behavior (TPB). A sample of native women in rural areas of Chabahar (n=152), who aged 12-75 years old, were selected by multistage sampling. Pre and post intervention measures of TPB variables, knowledge, and behavior were conducted via questionnaire. The educational intervention was performed with the help of high school girl students for the intervention group. There were positive significant changes in healthy cooking behavior intention, knowledge, subjective norms, perceived behavioral control, and behavior in the intervention group, while none of these changes were significant in the control group. The results suggest that educational intervention based on the theory of planned behavior can be effective in healthy cooking behavior of rural women of Chabahar.